The Impact of Compliance with International Standards (IFRS) On the Cost of Capital and Investment Decision to Maximize The Value of Companies Listed on the Palestine Stock Exchange - Rashwan, Abd El Rahman (The Arab Journal of Administration, 2019)
The study aimed to identify the impact of compliance with international standards (IFRS) on the cost of capital and investment decision to maximize the value of companies listed on the Palestine Stock Exchange. In order to answer the questions and test the hypotheses of the study, the researcher relied on the analytical descriptive method in clarifying and clarifying the theoretical aspect through previous studies, Analysis of the results of the field study and the testing of hypotheses using the statistical program (SPSS). The questionnaire was distributed after being evaluated and judged by a number of specialists on the sample of the study consisting of managers, heads of departments and accountants working in the financial departments of the investment companies listed on the Palestine Stock Exchange (53) employees and employees. The results of the study showed that compliance with international standards (IFRS) led to significant changes in the environment of companies listed on the Palestine Stock Exchange by improving the efficiency of these companies, increasing liquidity, reducing the cost of capital, enhancing transparency, protecting investors and reducing their fears of adopting and applying International Financial Reporting Standards (IFRS). The study also recommended the need to spread the culture of investment awareness suitable for investors and Palestinian investment companies to achieve compliance with the International Financial Reporting Standards (IFRS) of the benefits and benefits of investment at the local and international levels.